Food And Beverage Industry Sector Linkages In Indonesia - Junifer Tamin; Bernadette Robiani; M Teguh; Mukhlis Mukhlis (Equity: Jurnal Ekonomi, 2024)
The food and beverage industry in Indonesia is growing rapidly at the moment. Indeed, Indonesia is currently undergoing an economic transformation towards industrialization and services. Therefore, one of the factors that can support the acceleration of industrialization in Indonesia is to look at the linkages between the food and beverage industry sector, which makes the largest contribution to the manufacturing sector, and other industrial sectors. This study examines the linkages between the food and beverage industry and other manufacturing sectors, as well as the resulting income multipliers. The data used in this study is Indonesia's 2021 input-output data obtained from BPS. The analysis techniques used are descriptive analysis, linkage analysis, and multiplier analysis. The results showed that the food and beverage industry sector contributed 23.15% of the gross value added of the manufacturing industry. The IFL value of 1.1703 and the IBL value of 1.2092 indicate that the food and beverage industry has strong linkages with the downstream and upstream sectors. When multipliers, specifically income, are considered, each demand for the food and beverage industry of 1 rupiah, results in a total increase in income in the sector of Rp 345,911,027.